BODY AND NUTRITIONAL COMPOSITION INDICATORS OF STUDENTS FROM INSTITUTE FEDERAL OF EDUCATION, SCIENCE IS TECHNOLOGY OF THE CEARÁ (IFCE), CAMPUS JUAZEIRO OF THE NORTH (Fiep Bulletin - online, 2011)
The objective of this study is to compare investigation methods of the nutritional state through the body mass index and the body fat percentage of senior high school students. It results from a transverse study in a sample of 60 people (19 male and 41 female) with average age around 16 years old, from IFCE Juazeiro do Norte, CE. All of them underwent the body composition analysis through the triceps and subscapular skinfolds equating body fat percentage (BFP) in Slaughter equation, body mass and height to the body mass index (BMI). A statistics program was used to the descriptive and inferential analysis in test "t" of student to independent data, with a level of significance of 5%. The results found to the male and female genre were: BMI 21,6+3,15 e 20,95+2,75 and BFP 19,2+9,4, with no significant differences, being larger to the girls (w=0,002). The classification of the nutritional state through BMI indicated 75% with regular weight, whilst the BFP showed only 48.3% with an adequate classification and 50% were overweight. In conclusion, there are high levels of BFP to the girls, the opposite being true to the BMI. However, other body components and eating habits should be investigated, because if BMI is used as the only evaluation criterion of the nutritional state it can not eventually turn to be a good indicator to physically active people.
Keywords: people; body fat percentage; body mass index